Regional Competitiveness in Turkey - Emine Demet Ekinci hamamcı (İstanbul İktisat Dergisi)
The aim of this study is to determine the competitiveness indices of the sub regions according to NUTS2 level in Turkey and to estimate efficiency of these indices for creating GDP per capita. In this study, it has been taken into account four basic factors -economic structure, innovation, human capital, infrastructure and accessibility- that affect both the high competition and the level of GDP per capita. In this study, the methods have been followed Exploratory Factor Analysis (EFA) and Data Envelopment Analysis (DEA). Inputs of study are seventeen items related to four factors, whereas output item is per capita GDP. In the study, regional competition indices are firstly obtained with EFA. Then, by using DEA, it has been estimated efficiency of these indices for creating GDP per capita. According to the indices’ results of economic and innovative infrastructure, skilled labor infrastructure and regional basic infrastructure, TR10 İstanbul, TR31 İzmir, TR42 Kocaeli and TR51 Ankara are most competitive sub regions of Turkey. In the CCR Model, only three sub regions - TR10 Istanbul, TR42 Kocaeli and TR51 Ankara- have become efficient in generating per capita income, whereas eight sub regions -TR10 İstanbul, TR21 Tekirdağ, TR42 Kocaeli, TR51 Ankara, TR82 Kastamonu, TRA2 Ağrı, TRB2 Van and TRC2 Şanlıurfa- are efficient in the BCC Model.